A new species of Alonella Sars, 1862 (Crustacea: Cladocera: Chydoridae) from the Ecuadorian Andes - Alonso, Miguel; Kotov, Alexey (Zootaxa, 2017)
Several authors have pointed out that the Andean high altitude waters constitute a very interesting hotspot of biodiversity. Studies of these water bodies could significantly increase the number of Neotropical endemics among the Cladocera. One of the above mentioned taxa is described here as Alonella hampelae sp. nov. (Crustacea: Cladocera: Chydoridae). This new species belongs to the “excisaclathratula” group, characterized by the carapace strongly reticulated and bearing fine striae within the cells of reticulation, but presents several specific morphological characteristics. The most outstanding is the evenly rounded posteroventral angle of the valves that lack any denticles, which is unique within the genus Alonella Sars, 1862.